Strategic Planning of Urban Neighborhoods in Tehran (Case Study: Ferdowsi neighborhood of Region 12) - Amin Shahsavar; mousa kamanroodi; Taher Parizadi; Mahlagha Abolghasempor (تحقیقات کاربردی علوم جغرافیایی)
Urban neighborhoods play a major role in urban life and decline. The transformation of the relationship between mass and space and the changing in population and construction densities due to changes in lifestyle, population growth and ... has caused a major transformation in the spatial structure of the neighborhoods and, finally, amount of social communication and interaction at the local level. These inevitable changes in the neighborhood and the city have caused major problems in which according to the relationship between the spatial and social structure of urban neighborhoods, it is necessary to improve the situation on the other side by interfering and changing in each of the fields. In the present research, neighborhood-centered spatial development strategy and plan in Ferdowsi neighborhood have been investigated. This research in terms of purposing is applied; in terms of nature and method is prescriptive; according to type of data is quantitative and qualitative; and in terms of time, is cross-sectional. In this research, by using the AIDA technique and based on strategies and decision areas, a strategic project has been presented in order to empowerment of Ferdowsi's neighborhood.